English Medium Instruction in Taiwan: From the Perspective of International Students as Thesis Writer - Puspitasari, Dani; Weng, Cathy; Hsieh, Yu-Fen (International Journal of Language Education, 2020)
The establishment of English medium instruction (EMI) brings opportunities for non-native English speaking institutions to compete with Anglophone universities and attract international students to join their program. More policies were designed to improve the academic environment quality and attract international students. As a thesis becomes the graduation requirement, there is a weight of difficulties and high expectations to produce good writing. This study explores thesis writing problems and strategies perceived by L2 writers as international graduate students in Taiwanese EMI classrooms in Taiwan. The participants were 152 international students who pursued a graduate degree in Taiwanese tertiary education; their major was categorized into engineering and social studies. The data was collected through questionnaires and in-depth interviews with some participants. The quantitative result indicates both students across the major were experiencing the same challenges in thesis writing and utilizing similar strategies to overcome the problem. Later, the qualitative result provides explanations to what really happen among these graduate students while writing thesis. The result serves reference and suggestion for academics in assisting their supervisee. It also suggests to the university to assist these L2 writers by providing writing correction services to the betterment of the EMI programs in their institution.